The Role of Self-Awareness, Self-Control, and Spirituality in the Prevention of Social Harms Among Youth - Moshir Estekhareh, Seyed Naser (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: This study aimed to examine the role of self-awareness, self-control, and spirituality in the prevention of social harms among youth. Methods and Materials: A descriptive-correlational design with a predictive modeling approach was used. The sample consisted of 350 young people aged 18 to 29 years selected through multistage cluster sampling. Data were collected using the Self-Reflection and Insight Scale, Brief Self-Control Scale, Spiritual Well-Being Scale, Iranian Adolescents Risk-Taking Scale, and a demographic information form. Data were analyzed using Pearson correlation coefficients, hierarchical multiple regression, and structural equation modeling. Findings: Self-awareness, self-control, and spirituality were negatively associated with vulnerability to social harms (r = -.43, -.58, and -.49, respectively; p < .001). The hierarchical regression model was significant, F(6, 343) = 42.78, p < .001, and explained 42.8% of the variance. Self-control was the strongest negative predictor (β = -.37, p < .001), followed by spirituality (β = -.26, p < .001) and self-awareness (β = -.18, p = .002). The structural model showed acceptable fit, χ²/df = 2.22, CFI = .94, TLI = .92, RMSEA = .059, and SRMR = .046. Conclusion: Self-awareness, self-control, and spirituality appear to be important protective factors against vulnerability to social harms among youth. Prevention programs should strengthen reflective capacity, impulse regulation, meaning-making, and value-based decision-making.